2012
DOI: 10.1590/s1516-635x2012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between color and tannin content in sorghum grain: application of image analysis and artificial neural network

Abstract: The relationship between sorghum grain color and tannin content was reported in several references. In this study, 33 phenotypes of sorghum grain differing in seed characteristics were collected and analyzed by Folin-Ciocalteu method. A computer image analysis method was used to determine the color characteristics of all 33 sorghum phenotypes. Two methods of multiple linear regression and artificial neural network (ANN) models were developed to describe tannin content in sorghum grain from three input paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
3
27
0
2
Order By: Relevance
“…Response surface method (RSM) is one of the software that has been repeatedly used to optimize growth medium for in vitro culture of pear genotypes (Reed et al, 2013a,b; Wada et al, 2013, 2015). Previous studies detected that ANN-GA models had a substantially higher accuracy of prediction than RSM models (Sedghi et al, 2012). Moghri et al (2015) indicated that RSM alone is not trustworthy for approximation of non-polynomial or non-linear variables.…”
Section: Resultsmentioning
confidence: 94%
“…Response surface method (RSM) is one of the software that has been repeatedly used to optimize growth medium for in vitro culture of pear genotypes (Reed et al, 2013a,b; Wada et al, 2013, 2015). Previous studies detected that ANN-GA models had a substantially higher accuracy of prediction than RSM models (Sedghi et al, 2012). Moghri et al (2015) indicated that RSM alone is not trustworthy for approximation of non-polynomial or non-linear variables.…”
Section: Resultsmentioning
confidence: 94%
“…Response surface method (RSM) has been repeatedly used to optimization of new in vitro culture media for pear genotypes (Wada et al, 2013; Jamshidi et al, 2016). Previous investigations reported that ANN-GA models had a significantly higher accuracy of prediction than RSM and stepwise regression models (Ahmadi and Golian, 2011; Sedghi et al, 2012; Jamshidi et al, 2016). Moghri et al (2015) and Jamshidi et al (2016) indicated that RSM and regression models alone are not reliable for approximation of non-polynomial or non-linear variables.…”
Section: Discussionmentioning
confidence: 92%
“…CT) contribute to the dark color of canola meals. The tendency of tannin content to increase with intensity of seed coat color and it was reported that CT accumulation is most robust in young seed coats of black‐seeded line and only very little in the yellow‐seeded line …”
Section: Resultsmentioning
confidence: 99%